La satisfacción laboral y su influencia en la productividad de los trabajadores del IESS de la Dirección Provincial de Chimborazo. - Samaniego Samaniego, Diego Vladimir (2025)
The topic of this research, called Job Satisfaction and its Influence on the Productivity of IESS Workers of the Provincial Directorate of Chimborazo, is developed to correlate staff productivity with job satisfaction in the performance of duties at the Provincial Directorate of Chimborazo (DPCH) IESS. The study's main objective is to evaluate the relationship between the perception of employee satisfaction and their job performance within this public institution. This study's general objective is to evaluate how job satisfaction impacts the productivity of IESS workers to propose strategies that improve both aspects. To achieve this objective, a quantitative and descriptive methodology was used based on the application of structured surveys to a representative sample of employees. The data collected were analyzed to identify patterns and correlations between job satisfaction and productivity levels. The study's main results indicate a positive correlation between job satisfaction and productivity. Factors such as recognition, professional development opportunities, and a favorable work environment were highlighted as key elements that influence employee satisfaction. Furthermore, areas for improvement were identified, such as internal communication and reward management. In conclusion, the study confirms that improving job satisfaction can significantly increase employee productivity. Implementing the proposed strategies will contribute to creating a healthier and more efficient work environment, benefiting both employees and the organization. This project provides a solid foundation for future research and development in human talent management in the public sector.